PENILAIAN KINERJA PEGAWAI CV. SRI DENGAN MENGGUNAKAN METODE SIMPLE ADDITIVE WEIGHTING (SAW) - Sri Rejeki; Dwi Budi Srisulistiowati (JURNAL MITRA MANAJEMEN, 2022)
Performance appraisal evaluation factors, goal achievement and also work discipline (employee attendance) have difficulty in determining which employees are preferred for promotion. The problem for section heads is that they have not used a method that can handle priority issues with multiple criteria. In addition, because of the large number of employees to be evaluated, divisional managers often find it difficult to select the best employees. Constraints that often occur in the employee evaluation process are the lack of socialization about the work process, many employees do not understand the job description, there are elements of joy or sorrow between superiors and their respective subordinates, management policies that are less objective and many other regulations for the employee evaluation process are not there is openness, but with feelings and unilaterally according to the wishes of their respective superiors. Therefore, what is needed in the company is a decision-making method that can provide the best results in accordance with the expectations of employees and managers. The right method to determine employee performance appraisal is simple additive weighting (SAW). The results of this study are the results of a review of employees are very accurate compared to the manual method and also make it easier for department heads to report employee performance results. Thus, by evaluating employee performance, the work ethic of all employees can be improved, both for operational employees as well as employees and policy makers. Keywords: Employee; Performance assessment; Simple additive weighting